2013
DOI: 10.1097/psy.0b013e3182a0b664
|View full text |Cite
|
Sign up to set email alerts
|

A Life-Style Physical Activity Intervention and the Antibody Response to Pneumococcal Vaccination in Women

Abstract: Participation in a life-style physical activity intervention increased subjective and objective physical activity levels and quality of life but did not affect antibody response to pneumococcal vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Of these 17 studies, 16 were RCTs (highest level in the hierarchy of study designs [ 65 ]) and 1 was a quasi-RCT study (second highest level) [ 43 ]. In addition, 10 were categorized as high effective [ 32 , 39 , 41 , 45 , 48 , 49 , 51 , 60 , 61 , 63 ], 4 as low effective [ 32 , 37 , 44 , 57 ], and 3 as ineffective [ 35 , 43 , 52 ]. Additionally, 25 publications [ 32 - 36 , 38 - 43 , 46 - 51 , 54 - 59 , 62 , 63 ] included results on usability, 18 of which [ 32 , 33 , 35 , 36 , 38 - 43 , 48 , 49 , 51 , 54 , 56 , 57 , 62 , 63 ] were based on people’s experiences after having used the technology and 6 of which were based on expectations [ 34 , 46 , 50 , 55 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 17 studies, 16 were RCTs (highest level in the hierarchy of study designs [ 65 ]) and 1 was a quasi-RCT study (second highest level) [ 43 ]. In addition, 10 were categorized as high effective [ 32 , 39 , 41 , 45 , 48 , 49 , 51 , 60 , 61 , 63 ], 4 as low effective [ 32 , 37 , 44 , 57 ], and 3 as ineffective [ 35 , 43 , 52 ]. Additionally, 25 publications [ 32 - 36 , 38 - 43 , 46 - 51 , 54 - 59 , 62 , 63 ] included results on usability, 18 of which [ 32 , 33 , 35 , 36 , 38 - 43 , 48 , 49 , 51 , 54 , 56 , 57 , 62 , 63 ] were based on people’s experiences after having used the technology and 6 of which were based on expectations [ 34 , 46 , 50 , 55 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The medium most often used to execute the intervention was a mobile phone app [ 37 , 38 , 40 , 48 , 49 , 52 , 55 , 60 - 62 ]. Other mediums were a computer [ 35 , 39 , 43 , 45 , 54 , 63 ], a combination of computer and mobile phone for text messages (short message service, SMS) [ 32 , 41 , 42 , 44 , 51 , 57 , 58 ], a combination of computer and a mobile phone app [ 33 , 53 , 56 ], or just a mobile phone for text messages [ 56 ]. Finally, 10 interventions involved blended coaching [ 38 , 40 , 44 , 45 , 47 , 48 , 54 - 56 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…60-70% VO 2max 3-4 times per week, 25-60 minutes per session, for 10-12 months) [83][84][85] ; aerobic and resistance exercise 81 ; prescribed low-moderate intensity activities (taiji and quigong, 3 x 1 hour sessions per week for 20 weeks) 86 ; although benefit was not found in one study with an overall lifestyle intervention that also included physical activity. 87 The non-significant effects observed in the latter study may be related to study design (including participants' age:…”
Section: Vaccination Studiesmentioning
confidence: 99%
“…A number of the above-mentioned vaccination studies, which prescribed longterm physical activity, also reported a greater perceived quality of life compared to control groups. 80,88 This provides an additional mechanism by which exercise may enhance the response to vaccination as chronic psychological stress (e.g. also influencing quality of life measures) is also associated with decreased antibody response.…”
Section: Vaccination Studiesmentioning
confidence: 99%